Pengaruh media pendingin dan waktu pada perlakuan pack carburizing-quenching baja karbon rendah SS400 - Sujita, S.; Yudhyadi, I.G.N.K.; Zainuri, A.; Adhi, I.G.A.K.C.; Sutanto, R. (Dinamika Teknik Mesin: Jurnal Keilmuan dan Terapan Teknik Mesin, 2021)
The SS400 low carbon steel is widely used in the agricultural equipment industry because of its specific properties, malleability good corrosion resistance, and high strength to weight ratio. However, according to several research results it has several weaknesses, low surface hardness, ductility and wear resistance. Therefore, it is necessary to improve its mechanical properties so that the agricultural equipment products produced are of better quality. The purpose of this study was to determine the effect of variations in time and cooling media in the pack carburizing-quenching treatment of SS400 steel specimens. The pack carburizing treatment was carried out at a temperature of 875 ºC, 90 minutes, the carburizing medium was a mixture of corncob charcoal powder and Picntada maxima shell powder, with a composition of 70%: 30%, followed by a quenching process with variations in time (1, 2, 3, 4). minutes) and cooling medium (water, oil SAE 40, cane molasses 10% and  cane molasses 30%. The results of the study showed that the time and cooling medium affected the surface hardness, ductility and microstructure of the specimens With 30% cane molasses cooling medium, quenching time of 4 minutes, the largest specimen absorbed impact energy (toughness) is 2.23 J/mm2. On the other hand, the lowest surface hardness number is 285 Kg/mm2.The increased ductility causes the cracking marks to disappear on the specimen surface. Based on observations with SEM, there is a decomposition of the martensite structure with coarser grain sizes.